Discrimination of porcine and bovine gelatines based on reducing sugar types on Maillard reaction - Hamid, A.H.,; Ahmad Fadzillah, Nurrulhidayah; Abdullah Sani, Muhamad Shirwan; Muhammad, N.W.F; Othman, Rashidi; Rohman, Abdul (Rynnye Lyan Resources, 2020)
Increasing awareness among Muslims with respect to the Halal status of food has intensified efficient and effective food-source authentications that are science-basedprotocol. Traceability of gelatine to its source remains a daunting scientific task prior to classification of gelatine Halal status. The methodology of this study involves UV-Vis spectroscopic measurement of the degree of browning during Maillard reaction of different gelatine sources with the different type of reducing sugar. D-(+)-xylose has the highest value of browning value (A420nm) of Maillard reaction with gelatine among compared to another type of reducing sugar used. Principle Component Analysis (PCA) used to differentiate the sources of gelatine and successfully identify the major contribution of D-(+)-xylose in the browning value. The score plots of the first principle component (PC1) and the second component (PC2) could be classified and differentiated of gelatine types (porcine, bovine and fish) using variables of browning value of Maillard reaction of gelatinees with different types of sugar, as evaluated using spectrophotometer at 420 nm.